Matés Barco, J. M. y Caruana de las Cagigas, L. (coords.) (2021). Entrepreneurship in Spain. A History - Eduardo Martín Cuesta; Mauro Nahuel Cuk (América Latina en la Historia Económica, 2021)
Sin resumen